A study to examine the relationship between uterine pathology and depletion of oxytetracycline in plasma and milk after intrauterine infusion - Gorden, P. J.; Ydstie, J.; Kleinhenz, M. D.; Wulf, L. W.; Gehring, Ronette; Wang, C.; Coetzee, J. F. (My University, 2016)
Metritis is a frequent problem in postpartum dairy cows. Intrauterine therapy with oxytetracycline (OTC) is often used to improve therapeutic outcomes, although efficacy data supporting this therapy are ambiguous. Several manuscripts describe the depletion of OTC from milk following intrauterine therapy. However, none of these studies have correlated uterine severity scores with milk OTC concentrations using highly sensitive detection systems. Our objective was to do this to test the hypothesis that cows with more severe uterine severity would have higher OTC residues in milk following intrauterine therapy. Thirty-two cows received a single treatment of 4 g of OTC via intrauterine infusion. Blood and milk samples were collected before intrauterine therapy and throughout the trial period of 96 h after infusion. Uterine severity scores were assigned at initiation of therapy and every 24 h throughout the remainder of the trial. Plasma and milk samples were analyzed for OTC concentrations using liquid chromatography coupled with mass spectrometry. Following treatment, OTC rapidly diffused from the uterus to plasma and from plasma to milk. Maximum concentration in plasma and milk occurred within 24 h following intrauterine infusion and 18 of the cows still had detectable levels of OTC in milk 4 d after intrauterine infusion. Greater uterine severity score at the initiation of treatment showed a significant positively correlation with higher milk OTC concentration at the second milking following treatment (R2 = 0.46, P = 0.01) but there was no correlation between initial uterine severity score and OTC concentration at the conclusion of the study (R2 = ?0.06, P = 0.75). In the United States, intrauterine administration of OTC is considered to be an extra-label therapy. The use of uterine severity score can be used to predict OTC concentration in the first day following therapy but should not be used as a predictor of OTC concentrations 96 h after treatment. Dairy producers should consult with their veterinarian to develop strategies that will prevent the presence of violative residues of OTC in bulk tank milk following intrauterine therapy.
Citation: Gorden, P. J., Ydstie, J., Kleinhenz, M. D., Wulf, L. W., Gehring, R., Wang, C., & Coetzee, J. F. (2016). A study to examine the relationship between uterine pathology and depletion of oxytetracycline in plasma and milk after intrauterine infusion. Journal of Animal Science, 94, 30-30. doi:10.2527/msasas2016-065
Keywords: Bovine Metritis; Drug Residues; Agriculture